2020
DOI: 10.1186/s13098-020-00601-8
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome among children and adolescents in low and middle income countries: a systematic review and meta-analysis

Abstract: Background Metabolic syndrome (MetS) is a clustering of cardiovascular risk factors, which is rising in the low and middle income countries (LMICs). There are various studies with inconsistent findings that are inconclusive for policy makers and program planners. Thus, this systematic review and meta-analysis aimed at estimating the pooled prevalence of MetS and its components in LMICs. Methods Electronic searches were conducted in i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
3
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 110 publications
7
30
3
6
Order By: Relevance
“…The prevalence of MS in prepubertal children, which is lower than the prevalence reported in older children and adulthood, has been reported as ranging from 13% to 20% [50][51][52][53]. These results are in accordance with the data we found.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of MS in prepubertal children, which is lower than the prevalence reported in older children and adulthood, has been reported as ranging from 13% to 20% [50][51][52][53]. These results are in accordance with the data we found.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, a higher prevalence was reported among children with obesity in previous studies using the same MetS definition (52,53). Very recently, using IDF definition, Bitew et al (54) reported a pooled prevalence of MetS in low-and middle-income countries of 24.1% (95% CI: 16.90, 31.29) among children and adolescents with obesity. Similar to our study, almost 70% of the study subjects had abdominal obesity.…”
Section: Discussionmentioning
confidence: 88%
“…Waist circumference is directly associated with obesity and metabolic syndrome[ 23 , 24 ]. They are also the established risk factors of NAFLD.…”
Section: Discussionmentioning
confidence: 99%